Pengaruh Dana Desa Terhadap Tingkat Kemiskinan di Kabupaten Deli Serdang Sumatera Utara - Fidia Chairany Sitorus; Darwin Damanik (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to see how the influence of the realization of village funds on the poverty rate in Deli Serdang Regency. The sample in this study is 2022, using a combination of cross-sectional data and time series data. The results showed that village funds had an effect on the poverty rate of 18.8%. There is a simultaneous influence between the independent variable and the dependent variable and vice versa. However, between these two variables the poverty rate variable is greater than the poverty rate in Deli Serdang Regency. This can be seen from the results of the tests that have been carried out.